Exploring the Impact of Individual and Social Antecedents on Teachers’ Teaching Innovation: Perspective of Goal-Oriented Behavior and Social Identity - Cao, Caixia; Chen, Beibei; Yang, Suping; Zheng, Xu; Ye, Yan; Yue, Xiaoyao (Frontiers in Psychology, 2022)
Education management has been widely concerned by many scholars. Scholars in the education field have made great achievements in contributing to multiple educational reform policies, while some other scholars discuss teacher-related issues from the perspective of organizational behavior. Teaching innovation of high school teachers plays a critical role in learning attitude and motivation of students, especially in the context of COVID-19 pandemic. Teachers need to utilize more diversified teaching methods to enable students to carry out effective learning. In order to examine teachers’ teaching innovation, this study explores the teaching innovation intentions and performance from the perspective of individual and social factors in combination of the goal-oriented behavior and social identity theory. In this study, a sample of Chinese coastal high school teachers was conducted, and a total of 475 questionnaires were obtained. The research results show that innovation attitude, positive anticipated emotion, group norm and social identify positively affects teachers’ teaching innovation intention; and teachers' teaching innovation intention also positively affects their teaching innovation performance. Based on the comprehensive research findings, this research proposes corresponding theoretical and practical implications.